ARTISTIC FEATURES OF ABDULLA ORIPOV’S POETRY IN THE TRANSLATIONS OF SAIDALI MA’MUR AND BOZOR SOBIR (Eureka Journal of Language, Culture & Social Change, 2026)
This article describes the creative path of Abdullo Oripov, which can be divided into two periods, as they differ significantly from each other. The poet's poems are characterized by deep philosophical reflections, a variety of genres, a rich and imaginative language, and a close connection to the accessible folk language. Prominent contemporary poets in Tajikistan have recognized the artistic and stylistic features of this true master of the written word and have translated many of his poems into the Tajik language. Based on the analysis of the translation of the great Uzbek poet's poems into Tajik, it is safe to say that the act of re-creation and co-creation has taken place. There are noticeable linguistic transformations, but, most importantly, there are no semantic errors. Most importantly, there is a diligent effort to step in time with the music of the original. A. Oripov's translations have been poorly studied in the languages we compare, particularly in Uzbek and Tajik, and require further research. This article is intended for students, postgraduate students of philology departments (Russian philology, Uzbek philology, Tajik philology), philology teachers, linguists, and translators.
Keywords: imagery, genre, stylistic features, feelings, thought, and poetics.